Karakterisasi Simplisia dan Ekstrak Daun Pacar Kuku (Lawsonia inermis Linn) serta Penentuan Kadar Fenolat Total dan Uji Aktivitas Antioksidan - Elidahanum Husni; Netty Suharti; Arlyn Pasella Tri Atma (Jurnal Sains Farmasi & Klinis, 2018)
Lawsonia inermis Linn is the plants into the Lythraceae family. This plant has proven to be able to treat a variety of diseases. This research were aimed to identify the characterization of ethanol extracts and simplicia of  henna leaves, determine the total phenolic content with Folin-Ciocalteau method and antioxidant activity with Ferric Reducing Antioxidant Power (FRAP). The extraction was performed using 70 % ethanol. Characterization of simplicia was a powder, greenish brown color, bitter tasted and a distinctive odor. The loss of drying simplisia was 4.92 % ± 0.16, total ash was 4.61 % ± 0.02, acid insoluble ash was 4.43 % ± 0.14, water soluble concentration was 3.30 % ± 0.06, and ethanol soluble concentration was 25.46 % ± 0.18. Characterization of ethanol extracts was viscous, brown in color, typical odor and bitter tasted. The water content of ethanol extracts was 9.98 % ± 2.00, total ash content was 2.63 % ± 0.91, and non acid soluble ash content was 0.36 % ± 0.11. The results of the determination of the total phenolics of ethanol extracts was 16.02 g/100 g. And antioxidant activity of ethanol extract was 2.85 mmol Fe (II)/100 g